Practical aspects of etomidate use in the management of hypercortisolaemia. - Preda, V; Grossman, AB (2012)
We appreciate the letter from of Dr Soh et al. regarding our review on the use of etomidate in the treatment of Cushing's syndrome. We note that in their experience, our recommended dose regimen of 2.5 mg/h or thereabouts appears to be a safe and effective starting dose in most patients, and we note the utility and ease of use of the lipid formulation and its relative freedom from side effects compared with the more commonly used propylene glycol formulation; these are very helpful comments. Their experience in treating a further four patients is indeed further evidence of the usefulness of this agent.